2015
DOI: 10.5472/mmjoa.2803.02
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and BMI in obese children: One year follow up results

Abstract: Objectives: The aim of this study was to investigate the relationship between thyroid hormone levels and obesity, lipid levels and weight changes. Patients and Methods:Five to eleven year old normal weight, overweight and obese children underwent measurements of thyroid stimulating hormone (TSH), free thyroxine (fT4), lipid profile and autoimmune thyroid antibodies. Children with high TSH were reevaluated one year later without any intervention.Results: Three hundred children (126 obese, 74 overweight, 100 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Our study indicated that in pubertal girls with a higher serum TSH level had a higher risk of overweight/obesity based on BMI or WC measures, and the association was more evident for the BMI measure. Previous studies demonstrated that TSH was positively related to BMI-based obesity in pediatric outpatients ( 11 , 28 ), and WC-based obesity in adolescents ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our study indicated that in pubertal girls with a higher serum TSH level had a higher risk of overweight/obesity based on BMI or WC measures, and the association was more evident for the BMI measure. Previous studies demonstrated that TSH was positively related to BMI-based obesity in pediatric outpatients ( 11 , 28 ), and WC-based obesity in adolescents ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence suggests that thyroid dysfunction predispose to obesity, or vice versa ( 10 ). Overweight and obese children tend to have higher TSH levels ( 11 ). The association between adiposity and thyroid dysfunction may be modified by sex.…”
Section: Introductionmentioning
confidence: 99%
“…Ekinci et al has proved that higher TSH levels is associated with overweight and obesity in children [ 21 ]. In the present study, 22.27% (848/3808) of children were classified as overweighted and obese (13.18% for boys and 9.09% for girls).…”
Section: Discussionmentioning
confidence: 99%